Effects of selenium and vitamin E, in addition to melatonin, against oxidative stress caused by cadmium in rats - Konar, Vahit; Kara, Haki; Yilmaz, Mahmut; Dayangac, Alpaslan; Karatas, Fikret (Humana Press Inc, 2007)
The present study was carried to evaluate the protective effects of melatonin alone and vitamin E with selenium combination against high dose cadmium-induced oxidative stress in rats. The control group received subcutanous physiological saline. The first study group administered cadmium chloride (CdCl2) by subcutaneous injection of dose of 1 mg/kg. The second study group administered cadmium plus vitamin E with selenium (I mg/kg sodium selenite with 60 mg/kg vitamin E); the third study group administered cadmium plus 10 mg/kg melatonin (MLT); the fourth study group administered CdCl2 plus a combination of melatonin in addition to vitamin E and selenium for a month. Determination levels of plasma malondialdchyde (MDA), glutathione peroxidase (GSH-Px), blood superoxide dismutase(SOD), creatinine alanine transaminase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP), blood urea nitrogen (BUN), and urea were measured in serum. In only CdCl2 administered group, the MDA, creatinine, ALT, AST, ALP, and urea levels in the serum were significantly higher than the control group (p<0.05). Whereas in all other groups, this values were significantly lower than the only CdCl2 administered group (p<0.05). Erythrocytes GSH-Px, serum SOD activities of only CdCl2 received group were significantly lower than the control group (p<0.05). In conclusion, vitamin E + Se, melatonin and vitamin E, and Se, in addition to MLT combinations, had protective effects against high dose cadmium-induced oxidative damage.
Keywords: cadmium; oxidative stress; vitamin E; selenium; melatonin